USING CRITICAL READING TASKS TO IMPROVE STUDENTS’ READING COMPREHENSION AT SMA NEGERI 6 KOTA TIDORE KEPULAUAN - Kartini Safrudin; Saiful Latif; Anwar Ismail (Cakrawala Bahasa, 2023)
The research purpose to know the extent to which using critical reading tasks significantly develop students’ reading comprehension at SMA Negeri 6 Kota Tidore Kepulauan. This research used quantitative method by using pre-experimental design. By Varaprasad in Rajabi Tabatabaee (2015), the procedure of implementing critical reading tasks are: previewing, annotating, summarizing, analyzing, re-reading, and responding. The research sample involving 25 students of XI IPA, that chosen using simple random sampling technique. The data were collected from pretest and protest. The result of this research shows that the mean score of posttest is higher (83.2) than the pretest mean score (52.8). The value of the t-test (9.184) exceeds the t-table value (1.711) at the significance level of 0.05 and the degree of freedom of 24 using one tailed test. Thus, the alternative hypothesis (Hi) is accepted and the null hypothesis (H0) is rejected. It concludes that using critical reading tasks can significantly improve students’ reading comprehension, since there is significance difference between students’ reading comprehension score before and after using critical reading tasks to teach reading comprehension is given.